2013 IEEE International Symposium on Information Theory 2013
DOI: 10.1109/isit.2013.6620323
|View full text |Cite
|
Sign up to set email alerts
|

Arbitrarily small amounts of correlation for arbitrarily varying quantum channels

Abstract: As our main result we show that, in order to achieve the randomness assisted message -and entanglement transmission capacities of a finite arbitrarily varying quantum channel it is not necessary that sender and receiver share (asymptotically perfect) common randomness. Rather, it is sufficient that they each have access to an unlimited amount of uses of one part of a correlated bipartite source. This access might be restricted to an arbitrary small (nonzero) fraction per channel use, without changing the main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(69 citation statements)
references
References 20 publications
3
66
0
Order By: Relevance
“…Thus we consider in this work the correlation as resource, which is a much "cheaper" resource in the sense that we can simulate any (V , V ) correlation by common randomness asymptotically, but there exists a class of sequences of bipartite distributions which cannot model common randomness (cf. [18]). Now we consider the correlation assisted code.…”
Section: Fig 4 Avcqc When the Jammer Knows The Coding Scheme Havingmentioning
confidence: 99%
“…Thus we consider in this work the correlation as resource, which is a much "cheaper" resource in the sense that we can simulate any (V , V ) correlation by common randomness asymptotically, but there exists a class of sequences of bipartite distributions which cannot model common randomness (cf. [18]). Now we consider the correlation assisted code.…”
Section: Fig 4 Avcqc When the Jammer Knows The Coding Scheme Havingmentioning
confidence: 99%
“…After we indicated why the super-activation protocol works we do now want to switch the topic and highlight a few connections to related problems and technical difficulties: It is evident from the existing literature on AVCs [5], arbitrarily varying classical-quantum channels [14] and on the quantification of shared randomness [7,28,31,41,39] that the latter is not an easy task. A brief overview concerning the connections between quantification of shared randomness and arbitrarily varying channels has been given in [14].…”
Section: Models and Operational Definitionsmentioning
confidence: 99%
“…A brief overview concerning the connections between quantification of shared randomness and arbitrarily varying channels has been given in [14]. Our focus here is on systems that use only common randomness in various different ways.…”
Section: Models and Operational Definitionsmentioning
confidence: 99%
“…In [23], a classification of various resources is given. A distinction is made between two extremal cases: randomness and correlation.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, correlation is the weakest resource. The work [23] also puts emphasis on the quantification of the differences between correlation and common randomness and used the arbitrarily varying classical-quantum channel as a method of proof. It can be shown that common randomness is a stronger resource than correlation in the following sense: An example is given where not even a finite amount of common randomness can be extracted from a given correlation.…”
Section: Introductionmentioning
confidence: 99%